Operationalizing physical literacy for learners: Embodying the motivation to move - Ang Chen (Elsevier, 2015)
Physical literacy is a concept that is expected to encompass the mind and body in an integrated way to explain, promote, and help sustain human beings' fundamental function: movement. According to Whitehead (2010), physical literacy is defined by motivation, especially by competence-based and interest-based motivation. This point of view is consistent with vast amount of research evidence on children and adolescents' physical activity behavior. In the article I attempt to interpret and operationalize physical literacy from a perspective that children's motivation in physical education is both an innate mental disposition and an acquired/learned attribute. Particularly I rely on the conceptual learning theory and motivation regulation mechanisms of the self-determination theory to argue that in physical education, children should experience tasks that inspire them to embody competence and interest along with self-regulation strategies necessary for developing and sustaining the motivation to move.